Testing as a part of assessment formalization of student learning - V. A. Vizir; A. V. Demidenko; A. S. Sadomov; I. B. Prykhodko (Zaporozhye State Medical University, 2014)
Some pedagogical and methodical aspects of testing technologies usage within the framework of estimate procedures formalization of students' educational results are discussed in the article, general recommendations and requirements to the testing tasks are considered.